Pengaruh Pendapatan Asli Daerah (PAD) dan Belanja Pemerintah terhadap Produk Domestik Regional Bruto (PDRB) di Kota Jambi - Faradila Herlin; Muhammad Sabyan; Denada Aptiva Yeni (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of Locally Generated Revenue and Government Expenditure on the Gross Regional Domestic Product (GRDP) of Jambi City for the 2015–2024 period. The research method uses a quantitative approach with multiple linear regression analysis based on secondary data from the Central Statistics Agency. The results show that Locally Generated Revenue has a positive and significant effect on GRDP, while Government Expenditure has a positive but insignificant effect. Simultaneously, Locally Generated Revenue and Government Expenditure have a significant effect on GRDP of Jambi City for the 2015–2018 period.